COVID-19 crisis management of German ICU clinicians in leadership – a metaphor analysis - Piel, Julia; Hörold, Madlen; Brandstetter, Susanne; Drewitz, Karl-Philipp; Hrudey, Ilona; Schmitt, Rudolf; Apfelbacher, Christian (Frontiers in Public Health, 2023)
The COVID-19 pandemic coincided with an already long-standing crisis in health systems around the world characterized by economic pressure and increasing staff shortage. “Crisis” became a global metaphor to convey collective experiences of the COVID-19 threat. Little is known on how crisis metaphors influence thought and speech on crisis management and the challenging staff situation of intensive care unit (ICU) clinicians in leadership positions and how they act. Therefore, we were interested in (1) which metaphorical concepts ICU clinicians in leadership use to express experiences and strategies in dealing with coinciding crises, (2) how these change over time, and (3) how metaphors in speech reveal self-images of crisis management. We conducted a systematic metaphor analysis focusing on data from three participants of a qualitative interview study with twenty-four healthcare professionals in ICUs in Germany. The participants were interviewed at two time points between April 2020 and March 2021. We identified and reconstructed metaphorical concepts of three interviewees (ICU clinicians in leadership) with regard to the pandemic management, and developed a typology based on the dimensions of mood, modus operandi, location, and scope. The typology consists of eight self-images (protagonists) for the crisis management of ICU clinicians in leadership, such as the figure of the soldier (“to unite everyone behind this flag”), the distributor (“sometimes it is a crazy patchwork [wahnsinniges Gestückel]”) or the critic (“we are the fool for everything”). They embody different qualities of a leader and refer to intra- and inter-role conflicts within multiple crisis conditions. Metaphor analysis reveals different self-images of ICU leadership clinicians in relation to crisis management. This illustrates that thinking and perceptions of crisis management may strongly differ between and within leaders and may change over the course of crises. Our findings highlight the need both to improve knowledge on challenges associated with leadership in crises and preparedness, and to support clinicians in their leadership by recognizing and addressing differences and changes in leaders’ self-image.